2016
DOI: 10.1093/nar/gkw1030
|View full text |Cite
|
Sign up to set email alerts
|

IMG/VR: a database of cultured and uncultured DNA Viruses and retroviruses

Abstract: Viruses represent the most abundant life forms on the planet. Recent experimental and computational improvements have led to a dramatic increase in the number of viral genome sequences identified primarily from metagenomic samples. As a result of the expanding catalog of metagenomic viral sequences, there exists a need for a comprehensive computational platform integrating all these sequences with associated metadata and analytical tools. Here we present IMG/VR (https://img.jgi.doe.gov/vr/), the largest public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
199
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(200 citation statements)
references
References 33 publications
1
199
0
Order By: Relevance
“…In accordance with recent research efforts to elucidate the role of the rumen virome, a significant portion of the RUS-refDB proteins (switchgrass: 56; rumen fluid: 62) were assigned to the 913 viral scaffolds we recovered from our switchgrass-associated rumen metagenome 31,56 . Recent studies have demonstrated that some viruses contribute to polysaccharide degradation directly, as they encode glycoside hydrolases 57 , or indirectly through infection of carbohydrate-degrading microorganisms 5 .…”
Section: Virome Activity In Ruminant Biomass-degradationmentioning
confidence: 86%
“…In accordance with recent research efforts to elucidate the role of the rumen virome, a significant portion of the RUS-refDB proteins (switchgrass: 56; rumen fluid: 62) were assigned to the 913 viral scaffolds we recovered from our switchgrass-associated rumen metagenome 31,56 . Recent studies have demonstrated that some viruses contribute to polysaccharide degradation directly, as they encode glycoside hydrolases 57 , or indirectly through infection of carbohydrate-degrading microorganisms 5 .…”
Section: Virome Activity In Ruminant Biomass-degradationmentioning
confidence: 86%
“…The same study reported a circularized genome of 630 kbp in length, but this is an assembly artifact (SI and Figure S3 ). The problem of concatenated sequences was sufficiently prominent in IMG/VR (PaezEspino et al , 2017) that we did not include these data in further analyses. We used the complete and circularized genomes from our study and published phage genomes to depict a current view of the distribution of phage genome sizes (Methods).…”
Section: Genome Sizes and Basic Featuresmentioning
confidence: 99%
“…To determine if the Gossenköllesee PLVs were unique to high mountain lakes, or part of a globally dispersed group of viruses, we interrogated large metagenomic datasets using the novel MCP genes as bait. The complete IMG/VR protein dataset 38 40 . To enhance hits for matching viruses from these viromes, we downloaded all trimmed metagenomic reads from these two BioProjects from the European Bioinformatics Institute (EMBL-EBI; https://www.ebi.ac.uk/), re-assembled each individual metagenome and cross assembled 3 metagenomes (PRJEB19373) using SPAdes (settings: --meta -k 21,33,53,77).…”
Section: Public Metagenome Searchesmentioning
confidence: 99%